How Does a Cosplayer Integrate Personal Identity with the Personality of Their Chosen Character? (Cosplay Events after the Pandemic in Jakarta) - Putri, Shafa Ayuninda; Amiralda, Radhea Permata (Wacana Journal of Social and Humanity Studies, 2024)
This study is done to comprehend how cosplayers can integrate their personality with their chosen character. We have discovered a problem with cosplayers using a piece of popular culture to build their identities. Therefore, participatory observation and in-depth interviews were undertaken to solve the problem and learn more about the subject above. As secondary data, we checked the literature, conducted field observations, and interviewed informants for our primary data. Our research yielded information on several factors that influence cosplayers' behavior, the connection between cosplaying and character attraction, and other topics, benefits of cosplay, the need to conceal identity while becoming a cosplayer, the motivation behind concealing identity, the satisfaction of cosplay, the pandemic and its effect on cosplay events, and a comparison to the identification problems outside of Indonesia. The finding of this study shows that cosplayers participate in their hobbies to interact, unwind, and meet new people who share their interests. We concluded that cosplayers hide their identities because they don't want their cosplay activities to disrupt their regular lives. Keywords: self-identity, cosplay, pandemic, constructivism paragdim, phenomenology.